The Use of Indonesian Formal Language in the Process of Legislative Drafting in Accordance With Law Number 12 Of 2011 - Rati Riana; Muhammad Junaidi (Fakultas Hukum Universitas Hang Tuah, 2018)
The character of civil law law that gave birth to the form of written law perceived that the law relies on the text of the written text, so it is possible to misinterpret the interpretation or multiple interpretations of articles or regulations because of wrong in understanding the language. This will impact on law enforcement less than the maximum. The use of standard language is one solution to avoid multiple interpretations in understanding the essence of language in the realm of law. This type of research is qualitative research. The data source is the document of Law Number 12 of 2011 on the Establishment of Legislation. The analysis is conducted on the use of standard Indonesian language in the document to meet its accordance with the rules of the standard language. In addition to the document, the analysis was also conducted on the results of the interview and the questionnaire.